Macronutrient Contents and Yield of Cocoa Resulting from Two Different Rejuvenation Techniques - Meilani, Radhika Pingky; Putra, Eka Tarwaca Susila; Indradewa, Didik (Caraka Tani: Journal of Sustainable Agriculture, 2023)
Cocoa (Theobroma cacao L.) is one of Indonesia’s leading and important export commodities. The cocoa plant rejuvenation techniques aim to increase cocoa production and quality. Ring budding and side grafting can rejuvenate old and unproductive cocoa plants. Therefore, this research was conducted with objectives: 1) to record macronutrient contents, yield components and yields of three cocoa clones, KKM 22, RCC 70 and RCC 71, rejuvenated with ring budding and side grafting, 2) to determine the best techniques in rejuvenation program for old cocoa stand based on nutrient contents, yield components, and yields indicators of three cocoa clones. This research was carried out from November 2020 to January 2021 at Cocoa Plantation, North Segayung Production Unit, Pagilaran Company. The results showed that ring-budded plants had the highest N nutrients content in leaves, stem organic-C production capacity, pods number per stand per year, dry weight bean per stand per year and dry weight bean per hectare per year, which was significantly better than side grafted plants. The macronutrient of total parts (leaves, stem, and root) trend was leaves > stem > root. The trend of macronutrients in cocoa were organic-C > N > Ca > K > Mg > P. Based on the macronutrient content of cocoa tissue, KKM 22 have a higher content of organic-C, N, P, K, Ca, and Mg compared to RCC 71 and RCC 70. The budding ring technique was the best in the rejuvenation program for old cocoa stands based on nutrient contents, yield components, and yield indicators of three cocoa clones.